THE PHONOLOGICAL AND LEXICAL VARIATION OF LEMUKIH AND GALUNGAN DIALECT VIEWED FROM AGE DIFFERENCES: AN ANALYSIS OF SOCIO-DIALECTOLOGY - ., Gede Dharma Arya Wicaksana; ., Dr. I Gede Budasi,M.Ed,Dip.App.Lin; ., Nyoman Karina Wedhanti, S.Pd., M.Pd (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
This study aimed at exploring the phonological and lexical variation viewed from age differences which occurred in Lemukih and Galungan village. This research was a descriptive qualitative research. There were 10 informant samples from both Lemukih and Galunganvillage were chosen based on predetermined criteria. The data were collected based on researcher as the main instrument and four other additional instruments namely: observation, interview, word list and recording. The results of the study show that, 1) there is an indication of phonological variation such asunpacking,haplology, syncope, aphaeresis and apocope, 2) there is an indication of lexical variation such as semasiological variation,onomasiological variation,formal variation and contextual variation, 3) the reason of a tendency of dialect variation viewed by age differences in both Lemukih and Galungan dialect is the development of the technology which leads to the broader access into villages and begin to imitate dialects outside of one’s villages Kata Kunci : dialect,phonological variation, lexical variation, age differences This study aimed at exploring the phonological and lexical variation viewed from age differences which occurred in Lemukih and Galungan village. This research was a descriptive qualitative research. There were 10 informant samples from both Lemukih and Galunganvillage were chosen based on predetermined criteria. The data were collected based on researcher as the main instrument and four other additional instruments namely: observation, interview, word list and recording. The results of the study show that, 1) there is an indication of phonological variation such asunpacking,haplology, syncope, aphaeresis and apocope, 2) there is an indication of lexical variation such as semasiological variation,onomasiological variation,formal variation and contextual variation, 3) the reason of a tendency of dialect variation viewed by age differences in both Lemukih and Galungan dialect is the development of the technology which leads to the broader access into villages and begin to imitate dialects outside of one’s villageskeyword : dialect,phonological variation, lexical variation, age differences